A micropolar microplane theory - Etse, Jose Guillermo (2003)
The classical micropolar constitutive theory is reformulated within the framework of the microplane concept in order to obtain constitutive equations and models including available and, hopefully, more precise information of the complex microstructure of engineering materials like concrete and other composites. The main objective is the macroscopic modeling and description of anisotropic material response behavior by means of the well-developed microplane concept applied within a micropolar continuum setting. A thermodynamically consistent approach is considered to derive the so called micropolar microplane theory. The main assumption of the present proposal is the integral relation between the macroscopic and the microscopic free energy as advocated by Carol et al. [Int.J.Solids Struct. 38 (2001) 2921] and Kuhl et al. [Int.J.Solids Struct. 38 (2001) 2933] whereby the microplane laws are chosen such that the macroscopic Clausius–Duhem inequality is fully satisﬁed. This theoretical framework is considered to derive both elastic and elastoplastic micropolar microplane models.